Atendimento educacional especializado para estudantes com altas habilidades/superdotação: planejamento, perspectivas e desafios - Alves, Fernando Henrique Cordeiro (Universidade Federal de São Carlos, 2025)
Students with giftedness are eligible for Special Education and are entitled to Specialized Educational Assistance (AEE). Given the specific educational demands these students present, it is essential to implement educational adaptations to meet their learning and developmental needs. In this context, it is relevant to discuss how identification processes and supplementation strategies have been carried out within AEE, considering their importance for providing effective and qualified pedagogical support to students with AH/SD. The present research aimed to understand how pedagogical planning is structured to address the specific needs and perceptions of students with AH/SD in the context of AEE. The specific objectives were: (a) to analyze the pedagogical planning of teachers responsible for AEE for students with AH/SD; (b) to investigate students’ perceptions of the AEE they attend, including their experiences and the meanings they attribute to it. This study was characterized as qualitative and exploratory, conducted in accordance with ethical principles for research involving human subjects. Data collection took place in person at two public elementary schools (early years) in a medium-sized city in the state of São Paulo, involving five students identified with AH/SD and five AEE teachers, totaling ten interviews analyzed. Data analysis was conducted through transcription of the interviews, followed by content analysis, which enabled the identification of emerging categories and subcategories that reflected both teaching practices and students’ perceptions. The qualitative approach allowed for an in-depth understanding of the meanings attributed by the participants, supporting a critical interpretation of the practices and conditions surrounding AEE for students with AH/SD. The analysis revealed: the lack of teacher training and its direct impact on pedagogical practice with AH/SD students; the importance of building interinstitutional support networks to strengthen AEE; and the development and implementation of innovative teaching materials and methodologies aimed at this group. The final considerations pointed out that the expectations and specific needs of students with AH/SD are not being fully met in the context of AEE, as most of the activities offered remain limited to reinforcement in Portuguese Language and Mathematics, disregarding students’ areas of interest and potential. Furthermore, teachers reported significant challenges, such as the scarcity of specific continuing education opportunities, the lack of adequate infrastructure for services, and the shortage of diverse teaching resources, such as games and playful materials that foster curricular enrichment. Thus, it is concluded that AEE has not been able to fully meet the expectations and specific needs of these students.
Specialized educational services for students with giftedness: planning, perspectives, and challenges
Keywords: Educação Especial; Altas Habilidades/Superdotação; Educação Básica; Ensino Fundamental I; Planejamento Pedagógico; Special Education; Giftedness; Basic Education; Elementary Education– Early Years; Pedagogical Planning; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 4. Educação de Qualidade